Analisis Pinjaman Uang Online melalui Aplikasi Shopee Spinjam dalam Hukum Islam: Analysis of Online Money Loans via the Shopee Spinjam Application in Islamic Law - Giarti Rumailin; Muhibban (DIRASAH: Jurnal Kajian Islam, 2025)
Online money lending through applications such as Shopee Spinjam has become a rapidly growing phenomenon in the digital era, especially in meeting people's financial needs in a practical way. However, this service raises various questions regarding its compatibility with the principles of Islamic law. One of the main issues is the application of interest charged to users as well as the collection process in case of default. This study aims to examine concerns regarding the transparency of contracts, the validity of proposed terms and conditions, and potential ethical violations in the billing process, particularly in terms of Islamic law compliance. The research method employed is a qualitative approach with a descriptive design, encompassing a literature study and the analysis of secondary data in the form of testimonials and user reviews from various online platforms. This method is employed to explore the practical aspects of utilizing the Shopee SPinjam application. The results of this study indicate that Shopee SPinjam has implemented the conditions of qardh; however, there are still rules and practices that are not in accordance with Islamic law. he conclusion of this research is that there needs to be stricter regulations and education to the public regarding loans that are in accordance with Islamic law to avoid harmful practices.